A contrastive analysis of postnuclearity in English and Spanish: differences and similarities - Suárez, Nancy Adriana (2019)
The present thesis purports to analyze postnuclear patterns in English and Spanish\nwith a view to finding prospective differences and similarities. Moreover, particular\nreference is made to Gussenhoven?s classification of tails in English and to Ortiz\nLira?s comparative and contrastive approach to the study of such tails, both in English\nand Chilean Spanish. This provides us with the appropriate working framework on\nthe basis of which, utterances in River Plate Spanish will be analyzed.\nIn addition, the extensive literature available in English on this subject offers ample\nevidence of numerous cases of unaccented linguistic material in broad-focus tone\nunits.\nAs regards Spanish, curiously enough and in contrast with the traditional view,\nvarious cases of early nucleus placement can also be recorded in the River Plate\nlinguistic variety.